A concepção de Hare sobre as inferências práticas - Freitas, Adriano Nunes de (2009)
The theme of the present dissertation is situated in the fields of research of the Metaethics and of the Metajuridics. In these fields of research, we investigate the characteristics of prescriptive discourse (which include the Morals, the Law, and others) and in what aspects this discourse is different from descriptive discourse (which includes sciences like Physics, Mathematics, Chemistry, and others). The general problem that orientated the present research is the following: Is possible to use the principles of Logic as instruments to help in the systematization and evaluation of the discourses of Morals and Law? This general problem is divided in two specific problems: 1) What is the logico-semantical nature of the discourses of Morals and Law?; and 2) Can we make practical inferences, in which at least a premise and the conclusion are imperative sentences or norms? These questions get different answers depending on presuppositions adopted and the methods of analysis used. My purpose is to reconstruct, primarily, the answer given by R. M. Hare for these questions, and, secondarily, the answer given by H. Kelsen for these same questions. In the second and fourth chapters, I reconstruct Hare s argumentation in support of the thesis that it is possible to apply directly Logic to imperatives (norms). In third chapter, I reconstruct Kelsen s argumentation in support of the thesis that it is not possible to apply directly Logic to imperatives (norms).